2010
DOI: 10.1021/ic902279k
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Polymorphism and Decomposition of Y(BH4)3

Abstract: The structure and thermal decomposition of Y(BH 4 ) 3 is studied by in situ synchrotron radiation powder X-ray diffraction (SR-PXD), 11 B MAS NMR spectroscopy, and thermal analysis (thermogravimetric analysis/differential scanning calorimetry). The samples were prepared via a metathesis reaction between LiBH 4 and YCl 3 in different molar ratios mediated by ball milling. A new high temperature polymorph of Y(BH 4 ) 3 , denoted β-Y(BH 4 ) 3 , is discovered besides the Y(BH 4 ) 3 polymorph previously reported, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
115
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 40 publications
6
115
3
Order By: Relevance
“…However, it requires very tough conditions for rehydrogenation [3] and suffers from capacity loss on cycling due to the formation of higher boranes [4]. Another class of materials to be considered is rare earth (RE) borohydrides, with hydrogen capacities varying between 9.0 wt % for Y(BH 4 ) 3 and 5.5 wt % for Yb(BH 4 ) 3 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Li-containing RE borohydrides are also considered as solid state electrolytes for new battery applications, due to their high Li-ion conductivities [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, it requires very tough conditions for rehydrogenation [3] and suffers from capacity loss on cycling due to the formation of higher boranes [4]. Another class of materials to be considered is rare earth (RE) borohydrides, with hydrogen capacities varying between 9.0 wt % for Y(BH 4 ) 3 and 5.5 wt % for Yb(BH 4 ) 3 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Li-containing RE borohydrides are also considered as solid state electrolytes for new battery applications, due to their high Li-ion conductivities [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…13 However, no experimental evidence supporting the existence of Sc(BH 4 ) 3 is reported up to now. In contrast, Y(BH 4 ) 3 is found to crystallize in two different cubic polymorphs, one at room temperature 20 and one above 453 K. 22,23 On the other hand, scandium readily forms bimetallic homoleptic borohydrides based on the [Sc(BH 4 …”
Section: Introductionmentioning
confidence: 99%
“…The two phases have closely relatedcubic structures,the major difference is in the ordering schemes for the BH 4 anions and the deformation of the octahedral environment for the Yatom: in the low-temperature Pa " 3 3 phase it is distorted (Sato et al,2008), while in the high-temperature phase it is undistorted.F urthermore, the high-temperature phase is 4.6% less dense than the lowtemperatureo ne and contains relatively large unoccupied voids of 39 # A 3 ,accounting for almost aquarter of the volume. The metal atoms ubstructure in the high-temperature phase,d etectedb ys ynchrotron X-rayp owder diffraction, has the regularR eO 3 type (Ravnsbaek et al, 2010c). An independent studyb yn eutron powder diffraction (Frommen et al,2 010) revealed a Fm " 3 3 c superstructure with an ordered arrangement of the BH 4 groups,w here half of these are flipped to minimize H--H repulsion on the cost of al ess densely packeds tructure (Fig.…”
mentioning
confidence: 99%